2018
DOI: 10.3126/jcmsn.v14i1.18838
|View full text |Cite
|
Sign up to set email alerts
|

Reality of having bed nets at home, their status and pattern of using it at night among the population of Lakhantari Village Development Committee of Nepal

Abstract: Background & Objectives: The use of insecticide treated nets has been advocated for the prevention of the vector borne transmitted disease (malaria) by the World Health Organization and UNICEF for more than a decade. In spite of this, there is no significant reduction in the transmission of the disease. Main objectives of study were to find out the real pattern of using it, to find out the physical integrity of the bed nets being used, and to prove the correlation in between the physical integrity of bed nets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…A study conducted in Morang, Nepal, showed that almost all households had the mosquito nets, but just nine percent had no hole in the net. Similarly, four percent households had the mosquito nets with at least one hole and 25 percent had at least three holes in the net (Thapa et al, 2018). Such an instance shows that merely having the mosquito nets does not assure a proper application and protection as well.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Morang, Nepal, showed that almost all households had the mosquito nets, but just nine percent had no hole in the net. Similarly, four percent households had the mosquito nets with at least one hole and 25 percent had at least three holes in the net (Thapa et al, 2018). Such an instance shows that merely having the mosquito nets does not assure a proper application and protection as well.…”
Section: Discussionmentioning
confidence: 99%